2022
DOI: 10.1177/14713012221076954
|View full text |Cite
|
Sign up to set email alerts
|

Experience of UK Latin Americans caring for a relative living with dementia: A qualitative study of family carers

Abstract: Introduction Most studies of the Latin American immigrant experience and care for relatives living with dementia have been in the United States (US). In the United Kingdom (UK), unlike the US, most Latin Americans are first generation immigrants and are a rapidly increasing population. Therefore, we aimed to explore the UK experiences of Latin Americans caring for a relative with dementia. Methods We purposively recruited UK-based Latin American family carers of people with dementia ensuring maximum diversity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To fulfil these obligations, some sacrifices were needed around living arrangements and caregiving duties. Similar to a qualitative study on the experience of UK Latin Americans caring for a relative living with dementia, our participants emphasised the importance of fulfilling their familial obligations by providing care (Guerra et al, 2022). A systematic review of published empirical literature by Racine and team (2022) a study by Jacklin et al (2015) on informed dementia caregiving among Indigenous communities in Ontario, Canada, and results from Williams et al (2021) on the impact of dementia among American Samoan elders, strongly supported the findings from this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To fulfil these obligations, some sacrifices were needed around living arrangements and caregiving duties. Similar to a qualitative study on the experience of UK Latin Americans caring for a relative living with dementia, our participants emphasised the importance of fulfilling their familial obligations by providing care (Guerra et al, 2022). A systematic review of published empirical literature by Racine and team (2022) a study by Jacklin et al (2015) on informed dementia caregiving among Indigenous communities in Ontario, Canada, and results from Williams et al (2021) on the impact of dementia among American Samoan elders, strongly supported the findings from this study.…”
Section: Discussionmentioning
confidence: 99%
“…A more holistic approach to developing assessment tools and protocols for diagnosing dementia, as the LiDiA study is attempting, is clearly needed. Researchers worldwide are emphasising the need for culturally and linguistically appropriate screening tools (Lim et al, 2021), plus dementia information (Huggins et al, 2022) and services for minority ethnic groups (Guerra et al, 2022). For example, findings from a Māori dementia study (Menzies et al, 2021) showed that work embedded in cultural values improved the knowledge and understanding of dementia, known as mate wareware in Māori language, and could usefully inform the assessment of older Māori with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%